2018
DOI: 10.2196/mhealth.9145
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Health Applications to Improve Patient Experience: Cross-Sectional Study in Chinese Public Hospitals

Abstract: BackgroundThe proliferation of mobile health apps has greatly changed the way society accesses the health care industry. However, despite the widespread use of mobile health apps by patients in China, there has been little research that evaluates the effect of mobile health apps on patient experience during hospital visits.ObjectiveThe purpose of our study was to examine whether the use of mobile health apps improves patient experience and to find out the difference in patient experience between users and nonu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 21 publications
1
69
1
1
Order By: Relevance
“…Mobile health applications (apps) are rapidly proliferating and are widely used around the world to access health information 2 . In 2018, more than 50% of people worldwide had at least one mobile health app on their device 3 . There are more than 100,000 smartphone health apps available today.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile health applications (apps) are rapidly proliferating and are widely used around the world to access health information 2 . In 2018, more than 50% of people worldwide had at least one mobile health app on their device 3 . There are more than 100,000 smartphone health apps available today.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [18] also showed that women had slightly more positive attitudes and higher intentions to adopt mHealth, and they indicated that some other factors might also influence mHealth adoption intention. Lu et al [19] examined the user demographics of mHealth in 2016. They reported that the majority of mHealth users in China are young adults who are well educated and live in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile health apps industry growth had greatly changed the care services model. (Lu et al, 2018) (Ernsting et al, 2017) Health mobile applications have a function to offer people to access medical service easily (Lamprinos et al, 2014) The purpose of making the SATE Krembung application is to help reduce the mortality rate of pregnant women in the work area of Krembung community health center, Sidoarjo. By using smartphone applications that can provide education about pregnancy, and how to recognize danger signs for pregnant women.…”
Section: Discussionmentioning
confidence: 99%